Pengaruh Model Pembelajaran Student Facilitator And Explaining (SFE) Terhadap Peningkatan Hasil Belajar Aqidah Akhlak Kelas XI IPA DI Madrasah Aliyah Muhammadiyah 02 Pondok Modern Paciran Lamongan - Himmatul Husniyah (Jurnal Pendidikan Islam, 2022)
This study aims to determine the effect of the Student Facilitator and Explaining (SFE) learning model on im proving Aqidah Akhlak learning outcomes in class XI science. This study uses a quantitative approach with a total of 49 respondents, using sample data. Collecting data using pre-test and post-test questions. The collected data were analyzed by validity test, normality test, correlation test, and significance test. Based on the results of data calculations through the SPSS 23.0 for windows program. In testing the hypothesis, the researcher used the product moment correlation test, there was a positive effect using the Student Facilitator and Explaining (SFE) learning model on improving student learning outcomes, with r_xy=0.6228 rounded up to 0.623. Based on the results of the significance test above, it was obtained that tcount = 5.459 and ttable with 49 respondents at the average significant level of = 0.05 and dk = n-2 was obtained at 1.678. It can be concluded that there is an effect of the Student Facilitator and Explaining (SFE) learning model on improving Aqidah Akhlak learning outcomes in class XI IPA at MA Muhammadiyah 02 Pondok Modern Paciran.